And then comes pestilence: historical geography and epidemiology of infectious diseases after natural disasters - Fairley, Anna-Meagan (2018)
This thesis examines the dynamic of infectious diseases after natural disasters. Methods from epidemiology and geography intersect in the nexus of this research to form new insights into the risk of infectious disease in the aftermath of natural disaster and catastrophe. In the past decades, natural disasters have increased in frequency and magnitude, and with climate change progressing as it is, this trend is expected to continue. It is thus important to gain a fuller understanding of the dynamic between natural disaster and disease, and challenge the persisting problems in disaster and disease response efforts. Two approaches were taken to determine the risk of disease after disaster. Firstly, by pooling data from previously published literature, a form of meta-analysis was conducted to gain insight into risk patterns as well as to define relevant confounding factors that held significance in determining vulnerabilities of affected populations. For this analysis, a new tool was applied to identify relevant research, and this tool is expected to be useful in future study of the subject. Secondly, a set of empirical studies were conducted to determine the association between types of natural disasters, geographic region, and four distinct disease profiles. Cholera, malaria, tuberculosis, and the co-infection with HIV and tuberculosis served as examples for the types of diseases commonly observed after disasters (diarrhoeal diseases, vector-borne diseases, and acute respiratory infections). Logistic regression models were used to find the odds ratios for above average diseases at different tiers of disaster magnitude. It was shown in this research that the relative risk of infectious disease after natural disasters was 3.45, indicating a higher probability of disease after disasters. Specific results show that disasters affecting higher numbers of the population typically lead to increases in new infections. Most interestingly, tuberculosis relapses showed significant increases after natural disasters, especially meteorological and hydrological disasters.